3 highrise building projects: Shangai World Financial Center, Pudong Shangai China; 1994-2001; Roppongi Tower, Roppongi Tokyo Japan; 1992-2001; JR Central Towers, Nagoya Japan; 1990-1999 (A+U, 1996)
Edificio de oficinas por esl estudio <KPF>.